RESEPSI AL-QUR’AN SEBAGAI MEDIUM PENYEMBUHAN DALAM TRADISI BEJAMPI DI LOMBOK - Hasan, Muhammad Zainul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Al-Qur’an as a guide for Muslims necessitates interaction between people and verses of the Qur’an. The interaction between the Qur'an and Muslims gave birth to a diverse reception. Lombok Muslims’ reception of the Qur’an is manifested in a tradition called bejampi. Bejampi is a healing treatment using verses of the Qur'an. The use of the Qur’an for healing is rather contradictory to the advancement of medical knowledge. On this basis, this study tries to describe the motives that encourage the the practitioners to still preserve the bejampi tradition. To be able to identify these motives, this study uses a phenomenological approach with interpretive-explorative analysis. It concludes that bejampi tradition was born out of a practice called ngaji tau loqaq. The bejampi tradition in Lombok has strong historical roots and expresses a strong religiosity. Pejampi are those who have attended ngaji tau loqaq and comprehended hakikat and makrifat knowledge. In bejampi, the verses of the Qur’an are used to cure diseases, such as fever, stomach ache, headache, gout and eye pain. This reception is basically a form of cultural and exegesis receptions, which results from Lombok Muslims’ projection on the function of the Qur'an as a cure for all ills. This projection then becomes a cultural memory that forms the tradition of bejampi.